2015
DOI: 10.1007/s13337-015-0283-7
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective phylogenetic analysis of circulating BA genotype of human respiratory syncytial virus with 60 bp duplication from New Delhi, India during 2007–2010

Abstract: Human respiratory syncytial virus (hRSV) is the most common viral pathogen of acute lower respiratory tract infection in infants and young children. The G protein of hRSV is the trans-membrane glycoprotein that is involved in the attachment of virion with the host cell. The nasopharyngeal aspirates were subjected to RT-PCR for the second hypervariable region of the G protein gene in the present investigation. Sequencing and phylogenetic analysis revealed that all the study strains clustered within the BA genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
(40 reference statements)
2
14
1
Order By: Relevance
“…Two additional mutations were identified in the duplicated region of both BA and ON1 genotypes which indicates gradual accumulation of mutations over time in the duplicated regions of these genotypes as described earlier [76]. Therefore, it is obvious that evolutionary pressure exists on the duplicated regions suggesting more such genetic variations in the BA and ON1 genotypes in future.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Two additional mutations were identified in the duplicated region of both BA and ON1 genotypes which indicates gradual accumulation of mutations over time in the duplicated regions of these genotypes as described earlier [76]. Therefore, it is obvious that evolutionary pressure exists on the duplicated regions suggesting more such genetic variations in the BA and ON1 genotypes in future.…”
Section: Discussionsupporting
confidence: 55%
“…N- and O-linked glycosylation of the G protein are an important landmark of antigenicity of the virus because it may affect the expression of epitopes by either masking or facilitating the antibody recognition resulting in immune evasion [76]. Ten additional O-linked sites in the 24 amino acid duplicated region in ON1 and 2 additional O-linked sites in the 20 amino acid region in BA genotype were identified in the present study.…”
Section: Discussionmentioning
confidence: 61%
“…We analysed the BA9 lineage of BA genotype in detail since it was the predominant lineage. This analysis revealed global distribution of the BA9 genotype that was reflected across different geographical regions including India, Spain, Philippines, Thailand, South Africa, Japan, China, Vietnam, Ireland, Italy, Israel, Argentina, Iran, Germany, Cambodia and Malaysia [ 8 , 10 , 13 15 , 17 , 21 , 23 , 24 , 26 , 28 , 51 , 55 , 57 , 64 81 ]. Further, the studied SAB4 strains clustered with sequences from Cambodia [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the BA genotype dominated in Pune, Maharashtra during the years 2009–12 [ 23 ]. Consequently, the BA viruses from New Delhi attracted our attention during the years 2007–10 [ 28 ] and we continued our work on BA genotype throughout the years 2011–15. Interestingly, BA9 was the dominant lineage of the BA genotype identified in our study.…”
Section: Introductionmentioning
confidence: 99%
“…It has been postulated that N-and O-linked glycosylation of the G protein contribute to the antigenic variation in RSV thus assisting the virus in host immune evasion [63]. At least two N-linked glycosylation sites have been predicted for all the Saudi RSV strains belonging to each of the three genotypes that are reported from this region i.e.…”
Section: Glycosylation Site Analysismentioning
confidence: 99%